the Pharmacological Potential of East Kolaka Wild Honey as a Natural Anti-Inflammatory Agent: An In Vitro Study Based on Antioxidant Activity: Potensi Farmakologis Madu Hutan Kolaka Timur Sebagai Agen Antiinflamasi Alami: Studi In Vitro Berbasis Aktivitas Antioksidan - Nurfitriyana Rahmat; Syaiful Katadi; Poyizar Poyizar; Rahayu Aprianti; Muhammad Ramadan Salam; Irman Idrus (Jurnal Analis Kesehatan Kendari, 2026)
Chronic inflammation plays a significant role in various degenerative diseases and is often associated with oxidative stress. Black honey is known to contain bioactive compounds that possess potential anti-inflammatory properties through antioxidant mechanisms. This study aimed to evaluate the pharmacological potential of East Kolaka black honey as a natural anti-inflammatory agent based on its antioxidant activity and total phenolic content. This in vitro experimental study employed the Folin-Ciocalteu method to determine total phenolic content and the DPPH assay to measure antioxidant activity. All analyses were performed in triplicate. Data were analyzed using the Shapiro-Wilk normality test and Pearson correlation analysis with a significance level of p < 0.05. The total phenolic content of East Kolaka black honey was 33.1 ± 0.65 mg GAE/g. Antioxidant activity exhibited an IC₅₀ value of 48.7 ppm with a regression coefficient of determination (R²) of 0.963. A significant negative correlation was observed between total phenolic content and IC₅₀ values (r = -0.92; p = 0.018). East Kolaka black honey demonstrated strong antioxidant activity and possesses promising pharmacological potential as a natural anti-inflammatory agent through phenolic compound-based mechanisms. Further studies are required to confirm its biological effects using cellular and in vivo models.